Psychological well-being korban pelecehan seksual: Menguji peranan resiliensi dan dukungan sosial - Nadya Nikmah Wahyudi; Amanda Pasca Rini; Amherstia Pasca Rina; Nindia Pratitis (INNER: Journal of Psychological Research, 2023)
This study aims to determine the relationship between resilience and social support in psychological well-being in victims of sexual harassment. This research is a type of quantitative research using a correlational research approach. The sampling technique used was purposive sampling. The subjects of this study were 150 women who had experienced acts of sexual harassment domiciled in Surabaya. Data collection instruments using psychological well-being scale, resilience scale, and social support scale. The data analysis technique used was multiple linear regression analysis with the help of the statistical package for the social sciences (SPSS) 25.0 for the Windows program. The results of the data analysis show that there is a significant positive relationship between resilience and social support with psychological well-being in victims of sexual harassment. Keywords: Resilience, Social Support, Psychological well-being, Sexual harassment.